FIXED POINT RESULTS FOR JAGGI-TYPE HYBRID CONTRACTION IN JS-MODULAR METRIC SPACES - Zakariyya, Abdulaziz; Shagari, Mohammed Shehu; Mashina, Mohammed Sani (FUDMA JOURNAL OF SCIENCES, 2025)
In this paper, we introduce a new concept of JS-modular metric space and obtain some fixed-point results of hybrid contractions in this setting. Some corollaries that reduce our result to other well-known ideas in the literature are highlighted. An example is constructed to support the established concepts, and to demonstrate the distinction of this research with respect to the existing ones.
Keywords: JS-Modular Metric Space; Fixed Point